Analisis Nilai Tambah dan Saluran Pemasaran Pupuk Bioslurry Metroganik Untuk Menunjang Sistem Pertanian Terpadu - Zulkarnain, Zulkarnain; Supriyadi, Supriyadi; Isnaini, Soni; Rakhmiati, Rakhmiati; Mukhlis, Mukhlis; Prasetiani, Amalia Dwi; Yatmin, Yatmin; Maryati, Maryati; Krisnarini, Krisnarini (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The aim of this research is to analyze the value added and marketing channels of bio slurry fertilizer liquid metroganik at CV Harapan Bersama Rejo Agung Village East Lampung Regency. The research was conducted in CV Harapan Bersama, Rejo Agung Village, Batanghari District with a sample size of owner CV Harapan Bersama and 7 bioslurry fertilizer seller. The sampling method uses Purposive Sampling and the analytical method used in the research is Value Added Analysis with Hayami Method and marketing channels Analysis. The results showed that the added value obtained from biogas waste into metroorganic liquid bioslurry fertilizer was IDR 63,336.00 / product with a ratio of 80.79%. From the raw material price of IDR 4,063 / liter to IDR 80,000 with a profit of IDR 63,158.90 per product. The study concluded that livestock manure waste processed into liquid bioslurry fertilizer provides added value. Of the three existing marketing channels, marketing channel I is the most efficient marketing channel because it has the shortest marketing channel so that the profits obtained are greater.